2020
DOI: 10.2147/rmhp.s231075
|View full text |Cite
|
Sign up to set email alerts
|

<p>Development and Evaluation of an Educational Program for Community Pharmacists on Cardiovascular Risk Assessment</p>

Abstract: Purpose: Cardiovascular disease (CVD) risk assessment is an important strategy for the prevention of CVD. Pharmacists play an important role in CVD risk assessment and management (CVDRAM). Our previous study identified gaps in knowledge among community pharmacists for the provision of CVDRAM services as assessed through patient simulation. Therefore, our objectives were: a) to develop and evaluate an educational program on CVD risk assessment for community pharmacists, b) to assess the knowledge and skills of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These issues might be present because most studies do not utilize established frameworks to guide their evaluations. In fact, only 4 studies referenced the 4-level Kirkpatrick evaluation model [ 51 , 63 , 78 , 94 ], which is considered to be a widely used model for educational program evaluation [ 95 , 96 ]. However, of these studies, one completed only the first level of evaluation, another completed the first and second level of evaluation, a third completed the first to third levels of evaluation, and the fourth discussed “…an attempt to assess all 4 levels of Kirkpatrick’s evaluation framework…” though the depth to which this was done is questionable.…”
Section: Resultsmentioning
confidence: 99%
“…These issues might be present because most studies do not utilize established frameworks to guide their evaluations. In fact, only 4 studies referenced the 4-level Kirkpatrick evaluation model [ 51 , 63 , 78 , 94 ], which is considered to be a widely used model for educational program evaluation [ 95 , 96 ]. However, of these studies, one completed only the first level of evaluation, another completed the first and second level of evaluation, a third completed the first to third levels of evaluation, and the fourth discussed “…an attempt to assess all 4 levels of Kirkpatrick’s evaluation framework…” though the depth to which this was done is questionable.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by a study conducted in 2020 by Zolezzi and colleagues, who conducted a workshop series to educate CPs about CVD risk assessment measures. At the end of their study, the authors concluded that the educational programme had successfully improved CPs’ knowledge and skills related to CVD [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…So that, the mean score related to the observance of this principle was higher than the other principles from the model. In line with these findings, in Zolezzi et al’s study to develop and evaluate an educational program on CVD risk assessment based on the adult learning model, the learning needs of individuals in the educational process were considered and emphasized [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this andragogy principle, using active learning and involving adult patients in their health care and education, also making them feel responsible for their learning, has been emphasized in many studies to improve the outcomes of education and treatment [ 3 , 16 , 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%